2020
DOI: 10.3390/e22111239
|View full text |Cite
|
Sign up to set email alerts
|

Training Multilayer Perceptron with Genetic Algorithms and Particle Swarm Optimization for Modeling Stock Price Index Prediction

Abstract: Predicting stock market (SM) trends is an issue of great interest among researchers, investors and traders since the successful prediction of SMs’ direction may promise various benefits. Because of the fairly nonlinear nature of the historical data, accurate estimation of the SM direction is a rather challenging issue. The aim of this study is to present a novel machine learning (ML) model to forecast the movement of the Borsa Istanbul (BIST) 100 index. Modeling was performed by multilayer perceptron–genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 74 publications
0
26
0
1
Order By: Relevance
“… Optimized ANN model with crow search algorithm The MLP has many drawbacks such as slow convergence rate and stuck into the local minima. The training process and the convergence rate of MLP become more accurate when it is trained using a metaheuristic approaches like PSO 38 , 46 48 and GA 33 , 49 . However, CSA has been never investigated in training ANN.…”
Section: Methodsmentioning
confidence: 99%
“… Optimized ANN model with crow search algorithm The MLP has many drawbacks such as slow convergence rate and stuck into the local minima. The training process and the convergence rate of MLP become more accurate when it is trained using a metaheuristic approaches like PSO 38 , 46 48 and GA 33 , 49 . However, CSA has been never investigated in training ANN.…”
Section: Methodsmentioning
confidence: 99%
“…Deep learning scientists have often sought to improve the model's efficiency and loss function value by the model's training epochs. Stochastic gradient descent (SGD) is one of these approaches that give a single learning rate for all weight updates and does not modify the learning rate throughout the training 35 . Nevertheless, this method is not effective for the training model due to frequent fluctuations; it will keep overshooting near to the desired exact minima and very time‐consuming to converge to the correct network weights, which is inapplicable for online battery RUL prediction.…”
Section: Gru‐rnn‐oriented Rul Predictionmentioning
confidence: 99%
“…The use of ensemble models reported by some researchers found that ensemble models provide better performance than a single predictive model [40,67,68]. According to Fatih et al [69], there still is little research that has been done to predict the stock market using ensemble models.…”
Section: Machine Learning Techniquementioning
confidence: 99%
“…They used random forest and XGBoost classifier, and their study revealed ensemble models perform better if the proper combination of technical indicators is used as input features for a model. According to Ernest et al [69], the ensemble machine learning models provide superior results in comparison with any individual machine learning model. In their study, they focused on the tree-based ensemble models, and their models were trained with three different stock exchange datasets.…”
Section: Machine Learning Techniquementioning
confidence: 99%